Research on the Resilience Evaluation and Spatial Correlation of China’s Sports Regional Development Under the New Concept - Zhang, Jing; Gan, Jing-Ru; Wu, Ying; Liu, Jia-Bao; Zhang, Su; Shao, Bin (Frontiers in Psychology, 2022)
Abstract: In order to fully implement the new development concept, bring into full play the potential of sports development, and maintain the resilience of China's sports development. This paper studies the resilience evaluation and spatial correlation of Chinese sports development under the new development concept. Firstly, we construct Resilience Evaluation Indexes System for Sports Development in China based on the analysis of the resilience features of sports development and the DPSIR model,from five aspects of "driving force - pressure - state - influence - response". Secondly, used Coefficient of Variation and TOPSIS Method to measure the resilience level of sports development in 31 provinces in China during 2013-2017. Then, introduced the obstacle degree model to identify the obstacle factors that hinder the resilience of Chinese sports development in different periods. Finally, used the global and local Moran indexes to analyze the spatial correlation of China sports regional development. The results show that:①On the whole, the development level of sports resilience in 31 provinces in China showed an upward trend from 2013 to 2017, while some provinces showed obvious fluctuations.②The obstacles to the development of sports resilience in China mainly include sports scientific research equipment, the number of national fitness monitoring stations, the number of national fitness centers, the full-time equivalent of (R&D) personnel and the number of sports scientific research projects. The response subsystem is the main obstacle factor that affects the improvement of the resilience level of sports development in China. ③There is a positive spatial autocorrelation between the resilience level of sports development and regional spatial distribution, and the correlation shows a weakening trend, and the internal difference is significant. Finally, we come to the conclusion: We must take the new development philosophy as the guiding principle. First, we should stick to innovation-driven development to fully upgrade the resilience of China’s sports development. Second, we should adhere to the principle of coordinated development to promote overall and balanced development of sports.Lastly, we should promote shared development so as to deliver benefits for all in an equal way.